2015
DOI: 10.1371/journal.pone.0141004
|View full text |Cite
|
Sign up to set email alerts
|

Female Sexual Dysfunction in Women with Non-Malignant Cervical Diseases: A Study from an Urban Chinese Sample

Abstract: Non-malignant cervical diseases are common causes of disease among women worldwide. Although many studies have focused on sexual function in women with cervical cancer, little is known about the prevalence of female sexual dysfunction and its risk factors in women with non-malignant cervical diseases. The present study aims to assess sexual function in Chinese women with non-malignant cervical diseases and to identify potential risk factors for these diseases. A cross-sectional hospital-based survey was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…Ma et al (30) used the FSFI scale in patients with benign cervical pathologies and healthy controls. The prevalence of sexual pain in patients with benign cervical pathologies was lower than that of the controls.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al (30) used the FSFI scale in patients with benign cervical pathologies and healthy controls. The prevalence of sexual pain in patients with benign cervical pathologies was lower than that of the controls.…”
Section: Discussionmentioning
confidence: 99%
“…In this current study reported that half of cases get their menarche was (13)(14) and with duration (3)(4)(5) days, this study is supported by Koseoglu (2016) this study title was" Is There Any Impact of Copper Intrauterine Device on Female Sexual Functioning'' In this cross-sectional study subjects were divided into two groups IUD users group was nearly half and control group was nearly half. Both two gropes started their menarche between age (12)(13)(14) years with duration (3-5) days. In this study found that women in her feminine hygiene wash vagina with hot water only were nearly half of all cases and this because their little knowledge about practices of cleaning We found three quarter of cases using sanitary napkins than cotton because as they are more effective than cotton Regarding vaginitis found one quarter of cases have vaginitis.…”
Section: Discussionmentioning
confidence: 99%
“…Female sexual dysfunction (FSD) is regarded as a common health problem, which results from the interplay of multiple factors, such as age, race, menstrual status, relationships, mental health, etc. ( Ma et al, 2015 , 2014 ). It affects conjugal sexual relationships, which leads to interpersonal difficulties and causes obvious pain to patients ( Miller et al, 2018 ; Clayton and Valladares Juarez, 2019 ).…”
Section: Introductionmentioning
confidence: 99%